Maternal Social Support Is Associated with Child Complementary Feeding, and Household Food Security in the Vakinankaratra Region, Madagascar. (29th May 2020) - Komakech, Joel; Rakotomanana, Hasina; Walters, Christine; Hildebrand, Deana; Stoecker, Barbara
Abstract: Objectives: There is limited research on the associations between maternal social support and household food security and child feeding practices in Madagascar. Our study examined the association between maternal social support, household food security, and feeding practices among mothers of children 6 - 24 months in the Vakinankaratra region, Madagascar. Methods: This cross-sectional study included 344 mother-child dyads. The Medical Outcomes Study (MOS) Social Support Index was used for maternal social support scores. A mean score of >4 was considered optimal social support with ≤2 as none or little support. Food insecurity scores were determined using the Household Food Insecurity Access Scale (HFIAS). Complementary feeding practices were assessed using the World Health Organization (WHO) IYCF guidelines. Logistic and linear regression models tested the association between social support, complementary feeding practices, and household food insecurity. The models were adjusted for household, maternal and child confounders. Statistical significance was set at P  < 0.05. Results: Almost half of the mothers (49.1%) were supported by their spouses, although only 37.8% of mothers had optimal social support. Less than half of infants (36.34%) met minimum dietary diversity (≥4 of 7 food groups). Mothers with optimal social support had lower household food insecurity (b = −0.85, P  = 0.016, R, 2  = 0.10) in the adjusted models. Furthermore, children of mothers with higher social support were more likely to meet minimum dietary diversity scores (AOR = 2.36 [1.21–4.56], P  = 0.021) and to achieve the minimum adequate diet (AOR = 2.32 [1.17–4.61], P  = 0.018). Although maternal social support was significantly associated with child minimum meal frequency in the bivariate analysis, it became nonsignificant in the final adjusted model (AOR = 1.70 [0.93–3.11], P  = 0.387). Conclusions: Increased maternal social support was significantly associated with household food security, child dietary diversity, and diet adequacy. Integrating parental peer support in nutrition interventions may be effective in improving food security, and child feeding practices in the Vakinankaratra region of Madagascar. Funding Sources: This study was funded by Oklahoma State University.